A survey of attack and defense on human-computer interaction security - Kaiqiang GE; Tieming CHEN (Dianxin kexue)
With the development of technologies such as the internet of things and artificial intelligence,human-computer interaction applications are constantly being introduced.However,the development of human-computer interaction technology is also accompanied by new security issues,and human-computer interaction security attacks frequently occur.The status of four kinds of human-computer interaction technologies:HID-USB,fingerprint recognition,speech recognition and face recognition,as well as the offensive and defensive benefits were reviewed and analyzed,and the research direction of human-computer interaction security in the future was discussed.At the same time,some suggestions were given.